Arrest in South Africa of ships associated by common control of state-owned companies - Karimov, Bulat (Department of Commercial Law, 2025)
South Africa's associated ship arrest provisions permitting arrest of ships linked to the ship concerned by common control of the shipowning companies raise particular problems for shipowning state-owned enterprises in that if it is possible to arrest the ships due to common control of the state then all the ships belonging to state-owned companies are at risk to be arrested for the debts of each other. Depending on the number of state-owned companies in the country it may be a huge commercial fleet. It is argued that two situations should be differentiated. The first one is that the association between ships may be established due to common control of a state-owned company, the second one is where such an association is justified by common control of the state itself. It is concluded that, in the first case, the problem does not even arise since the ships are controlled by the company and it does not matter if such a company is state-owned or not. In the second situation, the problem reveals itself. The solution is suggested to exclude the ships linked to the ship concerned by common control of the state from the application of the relevant provisions of the AJRA 1983.